Elephant grass silage inoculated with cellulolytic fungi isolated from rumen - A.C.R. Veloso; H.F. Lopes; L.F.X. Santos; V.S. Martins Júnior; S.A. Fonseca; T.A.X. Santos; A.D. Matias; R.T. Careli; E.R. Duarte; T.G.S. Braz (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2023)
ABSTRACT The objective was to evaluate the inoculation with Aspergillus terreus and/or Trichoderma longibrachiatum on fermentation, chemical and microbiological composition of elephant grass ‘Cameroon’ silage (Cenchrus purpureus). Treatments were A. terreus at 105 colony forming units (CFU)/g (AT15), T. longibrachiatum at 105 CFU/g (TL20), a mixture of both at 105 CFU/g (MIX), and a control group without inoculation (CONTR). The design was completely randomized with seven replicates. The MIX silage was most stable, while CONTR, AT15, and TL20, had lower dry matter losses. There was no effect of inoculation in the chemical composition of silages. Only MIX silage (4.40) had pH above the minimum of 4.2 for humid grass silage and above the control (4.05). Bacteria from Diplococcus genus was identified at the opening of TL20 and CONTR silages. After air exposure, the population of rods, Lactobacillus, and total lactic acid bacteria was higher in theTL20 and MIX. The inclusion of a T. longibrachiatum and A. terreus mixture increases dry mater loss and silage pH. T. longibrachiatum was more efficient in maintaining populations of total lactic acid bacteria after opening; therefore, this strain has potential as an additive for elephant grass ‘Cameroon’ silage.